Teacher Ability Training in Developing Online Teaching Materials: Pelatihan Peningkatan Kemampuan Guru dalam Mengembangkan Bahan Ajar Online - Mochamad Sukardjo; Uswatun Khasanah; Yayan Sudrajat; Annis Kandriasari (Yayasan Ahmar Cendekia Indonesia, 2022)
Preparing face-to- face learning with teaching materials has often been done by teachers, but there are still many teachers who find it difficult to prepare and write lessons using online teaching materials. This training activity has the aim of improving the ability of teachers in compiling online teaching materials and increasing teacher creativity in online learning. This training method and strategy uses face-to-face (offline) discussions and questions and answers, as well as exercises and practices in compiling and writing online teaching materials. The results obtained after participating in this training are that all teachers want to be able to compose complete online teaching materials with a 100% questionnaire score. Furthermore, after participating in this training, the main priority in the future is the development of human resources (HR), this can be seen from 20 participants, then 20 participants (100%) chose to prioritize HR. Next, there are only 17 people (85%). Abstrak Mempersiapkan pembelajaran secara tatap muka dengan bahan ajar sudah sering dilakukan oleh guru, tetapi mempersiapkan pembelajaran dengan menggunakan bahan ajar online masih banyak guru yang merasa kesulitan dalam menyusun dan menulisnya. Kegiatan pelatihan ini memiliki tujuan untuk meningkatkan kemampuan guru dalam menyusun bahan ajar online dan meningkatkan kreativitas guru dalam pembelajaran online. Metode dan strategi pelatihan ini menggunakan tatap muka (luring) dengan diskusi dan tanya jawab, serta latihan dan praktik menyusun dan menulis bahan ajar online. Hasil yang diperoleh setelah mengikuti pelatihan ini adalah semua guru ingin dapat menyusun bahan ajar online secara lengkap dengan perolehan skor kuisioner 100 %. Untuk selanjutanya setelah mengikuti pelatihan ini yang menjadi prioritas utama dimasa yang akan datang adalah pengembangan sumber daya manusia (SDM), ini terlihat dari 20 peserta, maka ke 20 peserta(100%) memilih memprioritaskan SDM. Berikutnya baru masalah dana sekiatr 17 orang (85%).